Mortalité et cyclones en Guadeloupe (Antilles françaises) - Frédéric Leone; Samuel Battut; Victoria Bigot; Guilhem Cousin Thorez; Thomas Candela; Freddy Vinet (EchoGéo)
This paper lays the methodological basis for a historical catalogue of significant and deadly hydro-meteorological events that have occurred in the Guadeloupe archipelago and the northern islands since 1635. For the recent period, post 1950, it is supplemented by a Geographical Information System used to locate and inform each victim with his profile, his behavior, the circumstances and causes of death. In addition to the contribution of consolidated human death tolls, this new geo-historical framework makes it possible to analyze the evolution of mortality over time in relation to the main factors of vulnerability. A number of useful lessons can be drawn from this to guide risk prevention in Guadeloupe.